A Monoclonal Antibody that Recognizes the Receptor Binding Region of Human Urokinase Plasminogen Activator - Luisa Nolli, Maria; Corti, Angelo; Soffientini, Adolfo; Cassani, Giovanni (Thrombosis and Haemostasis, 1986)
An anti-urokinase monoclonal antibody 5B4 (MAB 5B4) was obtained by fusing the murine myeloma cell line X63-Ag8.653 with the spleen cells from a female BALB/c mouse immunized with high-molecular-weight urokinase (HMW-uPA).MAB 5B4 is an IgGl that binds selectively to the single-chain form of uPA (sc-uPA), to HMW-uPA and to the 17,000 Mr aminoterminal fragment of the A-chain (ATF) but not to the low-molecular-weight urokinase (LMW-uPA) nor to the reduced form of HMW-uPA. This strongly suggests that MAB 5B4 recognizes a conformational determinant on the A-chain.The antibody has an affinity constant for uPA-Sepharose of 1.42 × 107 M−1, calculated from equilibrium binding data, and can be used for one step purification of HMW-uPA by immunoaffinity chromatography.MAB 5B4 and the previously obtained antibody 105IF10 (16) recognize the A-chain: the epitopes, however, are distinct as shown by double-antibody-sandwich enzyme immunoassay.Finally MAB 5B4 inhibits the binding of ATF to the uPA receptor of different human cells, whereas 105IF10 does not. Thus this antibody represents a potentially, useful tool for the study of uPA receptor physiology.
Keywords: Urokinase; Urinary plasminogen activator; Fibrinolysis; Monoclonal antibody; Receptor